3х-2=-х+7 4х-4=-х+5 3х-6=2х-[latex] \frac{1}{3} [/latex] 2х-7=3х+[latex] \frac{1}{4} [/latex] 7х=-95,4-2х 0,3(х-2)=0,6+0,2(х+4) 0,8(х-2)=0,7(х-1)=2,7 0,6(х+7)=0,5(х-3)+6,8 [latex] \frac{x+4}{6}= \frac{3x-2}{7} [/latex] [latex] ...

3х-2=-х+7 4х-4=-х+5 3х-6=2х-[latex] \frac{1}{3} [/latex] 2х-7=3х+[latex] \frac{1}{4} [/latex] 7х=-95,4-2х 0,3(х-2)=0,6+0,2(х+4) 0,8(х-2)=0,7(х-1)=2,7 0,6(х+7)=0,5(х-3)+6,8 [latex] \frac{x+4}{6}= \frac{3x-2}{7} [/latex] [latex] \frac{x-3}{2,4}= \frac{7}{1,2} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
10х-2=7х 9х-4=5х 1х-6=х ,........... 5х=95,4
Не нашли ответ?
Ответить на вопрос
Похожие вопросы